Customer perception of Kedai Rakyat 1 Malaysia (KR1M) at selected outlet in Malaysia / Lina Syamimi Abu Bakar, Mohd Nurhairi Mohd Hassan Ng and Nor Ernizajura Jusoh - Abu Bakar, Lina Syamimi (2013)
This study on Customer perception of Kedai Rakyat 1 Malaysia (KRIM) are aim to identify the customer acceptance of the services provided in terms of prices, products, promotions and also the location place by the selected Kedai Rakyat 1 Malaysia in Terengganu and Kelantan and also to enhance the perception of the customers towards of services quality and productivity of Kedai Rakyat 1 Malaysia (KRIM)